Hedonic and Utilitarian Aspect of Traditional Retail Shopping - Yilmaz, Mustafa Atahan; Koçoğlu, Duygu (European Scientific Journal, ESJ, 2018)
Consumption consists of quite different concepts compared to the recent past consumption patterns. Traditional retailing has been evolving into online shopping which is getting out of timing/placing limits in this process. This transformation force traditional retailers to present something more than a mere shopping. This research aims to investigate face-to-face shopping from traditional retailers in contexts of hedonism and utilitarianism. A total of 263 respondents participated in the survey. As a result, there were no significant difference between male and female consumers in traditional retail shopping on the utilitarian aspect, but the difference for hedonism were significant. Female customers tend to shop more hedonic. Marital status does not affect the hedonic or utilitarian aspect; but there was significant difference found between employed and unemployed consumers. Unemployed consumers were found to be more hedonic in traditional retail shopping behavior.